2021
DOI: 10.1038/s41562-020-01019-y
|View full text |Cite|
|
Sign up to set email alerts
|

The genomics of childhood eating behaviours

Abstract: Eating behaviors may be expressions of genetic risk for obesity and are potential antecedents of later eating disorders. However, childhood eating behaviors are heterogeneous and transient. Here we show associations between polygenic scores for body mass index (BMI-PGS) and anorexia nervosa (AN-PGS) with eating behavior trajectories during the first ten years of life using data from the Avon Longitudinal Study of Parents and Children (ALSPAC), N=7,825. Results indicated that one standard deviation (SD) increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 48 publications
2
11
0
Order By: Relevance
“…Results are in line with previous longitudinal evidence for a causal influence of personality and psychopathology measures on childhood obesity (Anzman-Frasca et al, 2015; Blaine, 2008; Camfferman et al, 2016; Christensen et al, 2019; De Decker et al, 2017; Derks et al, 2019; Korczak et al, 2013) as well as studies suggesting obesity and eating behavior to have a bidirectional relationship (Antoniou et al, 2016; Herle et al, 2021; Reed et al, 2017). Some studies suggested that childhood obesity may also influence psychopathology (Bradley et al, 2008; Hübel et al, 2019; Korczak et al, 2013).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Results are in line with previous longitudinal evidence for a causal influence of personality and psychopathology measures on childhood obesity (Anzman-Frasca et al, 2015; Blaine, 2008; Camfferman et al, 2016; Christensen et al, 2019; De Decker et al, 2017; Derks et al, 2019; Korczak et al, 2013) as well as studies suggesting obesity and eating behavior to have a bidirectional relationship (Antoniou et al, 2016; Herle et al, 2021; Reed et al, 2017). Some studies suggested that childhood obesity may also influence psychopathology (Bradley et al, 2008; Hübel et al, 2019; Korczak et al, 2013).…”
Section: Discussionsupporting
confidence: 91%
“…An experimental study observing brain morphology changes following bariatric surgery found an effect of childhood obesity on cortical thickness (12). Genetically informed analyses revealed directional effects from polygenic scores for BMI to ADHD, heavy smoking (42), and overeating (43), as well as cortical volume (44). Schizophrenia and anorexia nervosa genetic propensity were identified to predict childhood obesity (42).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 44 , 45 , 46 Research also indicates that a higher PGS for AN is associated with emotional eating 44 and childhood fussy eating. 47 Taken together, several sources of converging evidence suggest that polygenic risk for AN and/or BMI may impact growth at least in part via eating behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…The PGS-BMI is a broad indicator of genetic propensity for higher BMI and might influence later body size through multiple metabolic and behavioral pathways. Previous research has indicated that childhood eating behaviors and childhood body size share some genetic etiology [ 41 ], including a recent study in this sample proposing that the PGS-BMI is associated with longitudinal patterns of overeating [ 42 ]. Other potential pathways in childhood might be physical activity, screen time, and dietary intake [ 43 ].…”
Section: Discussionmentioning
confidence: 99%